A bola no "pé do morro": o futebol como campo de possibilidades de lazer no Morro do Papagaio em Belo Horizonte – MG - Felipe Vinícius de Paula Abrantes (2021)
The main objective of this research was to analyze the presence of football in the community of Morro do Papagaio, in Belo Horizonte, as well as to assimilate the ways in which this practice manifests itself as an alternative leisure activity and sociability for residents of the cluster and visitors to Parque Jornalista Eduardo Couri. As auxiliary objectives, the study sought to understand community football as a catalyst for other activities and leisure experiences in the park, understand the organization of matches and tournaments and its relationship with the community, analyze the functioning of amateur football clubs present in the cluster and identify the uses that are made in the park in general. For this purpose, the work made use of methods used to ethnographic research, such as participant observation and subsequent records in the field notebook (MAGNANI, 1997), interviews, image records and dialogues with community residents. The data obtained were previously organized for further analysis. The interpretation of the information took place in the light of the proposal of a dense description (GEERTZ, 1989). For this, the tips for this interpretation, given by the "natives" were followed and used for the analysis. At the time of data analysis, categories of organization and interpretation of the material were listed, namely: the community/football relationship, sociability and leisure in the park, community/club membership and uses and appropriations that are made in the Parque Jornalista Eduardo Couri. The main results obtained by the survey reveal how the Morro do Papagaio community organizes itself and in a way ensures that leisure is experienced by local people. For this, community football proved to be an important ally. The existence and organization of football teams in the community, tournaments and festivals that take place in the park are widely used by the population as a way to access moments of leisure and enjoyment. The relationship between the community and community football proved to be quite intense, in the case of the Prointer team, this issue is even more noticeable, and made the club to be understood as an expression of belonging to the community, a community belonging. Furthermore, the investigation allowed, based on the reality found in Prointer, to make a broader reflection on women's football in Brazil. Regarding the uses of the park that are made, in addition to the soccer fields, the research showed that there is a kind of social barrier between the different groups that use public equipment. Both, with regard to the places they access, and in relation to the activities chosen by these different groups, for leisure within the park. Regarding the role of public authorities in promoting leisure for the population, I understand that there is a lack of clarity on the part of this administrative entity, in understanding the demands of the community and thus proposing public policies that address these expectations.